1990
DOI: 10.1144/gsl.sp.1992.049.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Chronostratigraphy of the Cretaceous carbonate shelf, southeastern Arabia

Abstract: Carbonate deposits dominated the southeastern part of the Arabian Shelf from Berriasian to Santonian time, approximately 60 Ma. Deposition was terminated by the development of the Oman Foredeep in Coniacian-Santonian following the initial emplacement of the Hawasina and Semail nappes in the Turonian. The Lower and middle Cretaceous units in Arabia correlate with European reference sections and the current ages of the stage boundaries can be used to form a quantitative scale.The Thamama-Kahmah Group to the Ilam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
3

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 27 publications
1
73
0
3
Order By: Relevance
“…Remark.-The Rayda facies cannot be regarded as a lateral equivalent of the Salil facies as erroneously interpreted in HAAN et alii (1990, Fig. 11), SCOTT (1990, Fig. 7), etc..…”
Section: -Rayda Formationmentioning
confidence: 94%
“…Remark.-The Rayda facies cannot be regarded as a lateral equivalent of the Salil facies as erroneously interpreted in HAAN et alii (1990, Fig. 11), SCOTT (1990, Fig. 7), etc..…”
Section: -Rayda Formationmentioning
confidence: 94%
“…On their side, based on subsurface log signature, petroleum geologists subdivided the Natih Fm. into seven informal "members" (reservoir units) designated by the lowercase letters "a" to "g" from top to base (Hughes Clarke, 1988;Scott, 1990). Although labeled in a reverse stratigraphical order, the recombination of these subsurface informal units into outcropping lithostratigraphic "members" got soon extensively used (e.g.…”
Section: Lithostratigraphymentioning
confidence: 99%
“…In Oman, this succession was described as the Natih Formation and is classically attributed to the upper Albian to lower Turonian (Simmons and Hart, 1987;Smith et al, 1990;Scott, 1990;Kennedy and Simmons, 1991;Philip et al, 1995;Van Buchem et al, 2002;Homewood et al, 2008). The Natih Fm.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 3 summarizes the stratigraphy of the Aptian to Miocene succession in onshore Abu Dhabi (Alsharhan and Kendall, 1991;Alsharhan and Nairn, 1988, 1990, 2003van Buchem et al, 2011) and Oman (Forbes et al, 2010). Maximum flooding surfaces (MFSs) recognised in the Arabian Plate (Sharland et al, 2001;Sharland et al, 2004) are also shown and are approximately dated using the Geological Time Scale of Gradstein et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…The base is bounded by the middle Turonian (MT) unconformity, located between the Laffan and Shilaif Formations. This unconformity marks a period of emergence and erosion which occurred as a result of stacking of the obducted thrust sheets, which in turn caused loading, flexural subsidence and partial erosion of the underlying shelf carbonates (Wasia Group) (Alsharhan and Nairn, 1990;Harris et al, 1984;Robertson and Searle, 1990;Scott, 1990). The succession is bounded above by the Cretaceous -Tertiary (K-T) boundary which was formed due to a eustatic fall in sea-level.…”
Section: Geological Settingmentioning
confidence: 99%